Rural development and aging: case study in Chinavita, Boyacá, Colombia - López, Érica Paola; Martínez, Lina Marcela; Martínez-Cañas, Camilo Andrés; Vargas-Prieto, Amanda (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The objective of this research is to determine the implications of aging of people on the development of Boyacá State, analyzing the period between 1985 and 2005 as historical data and from 2006 to 2020 as estimated data. For this purpose, we used a case study carried out in the municipality of Chinavita, province of Valle de Tenza in Boyacá, Colombia. The application of the methodology allowed determining that there is a direct relationship between economic growth and the migration processes of the younger population, which directly impacts on the profitable capability of the municipality. In this sense, some of the most important factors that cause high levels of migration are the lack of opportunities for employment and education opportunities in rural areas. In addition to this, potential risks in the sustainability of both the social security and protection system and besides, public finances aimed to elderly care programs. The absence of formal employment, which allows young people to contribute to the social security and protection system, reveals a possible crisis in the pension system. In this context, it is shown the need for a serious and responsible state policy that addresses the issue of aging of people in a comprehensive manner.